Sustained Neurog3 expression in hormone-expressing islet cells is required for endocrine maturation and function - Wang, Sui (National Academy of Sciences, 2009)
Neurog3 (Neurogenin 3 or Ngn3) is both necessary and sufficient to induce endocrine islet cell differentiation from embryonic pancreatic progenitors. Since robust Neurog3 expression has not been detected in hormone-expressing cells, Neurog3 is used as an endocrine progenitor marker and regarded as dispensable for the function of differentiated islet cells. Here we used 3 independent lines of Neurog3 knock-in reporter mice and mRNA/protein-based assays to examine Neurog3 expression in hormone-expressing islet cells. Neurog3 mRNA and protein are detected in hormone-producing cells at both embryonic and adult stages. Significantly, inactivating Neurog3 in insulin-expressing β cells at embryonic stages or in Pdx1-expressing islet cells in adults impairs endocrine function, a phenotype that is accompanied by reduced expression of several Neurog3 target genes that are essential for islet cell differentiation, maturation, and function. These findings demonstrate that Neurog3 is required not only for initiating endocrine cell differentiation, but also for promoting islet cell maturation and maintaining islet function.